When old becomes new: a case study of oral examination as an online assessment tool. Issue 8 (16th November 2020) - Akimov, Alexandr; Malin, Mirela
Abstract: Assessment is an important element of any effective teaching and learning strategy. Designing an appropriate assessment strategy is a continual challenge for instructors because the assessment structure must be well aligned with the intended learning outcomes. Technological advances have led to an expansion of online and distance modes of course delivery and brought new challenges, such as accessibility and legality, identity security and academic dishonesty. This study describes the application of an oral examination as a form of assessment in the online context. The findings demonstrate that oral examination can assist in overcoming some of the challenges associated with online learning. However, careful planning is required to ensure that it meets the principles fundamental to a successful assessment strategy: validity, reliability and fairness.